Discovery of a new class of valosine containing protein (VCP/P97) inhibitors for the treatment of non-small cell lung cancer. Issue 3 (1st February 2019) - Wang, Xueyuan; Bai, Enhe; Zhou, Hui; Sha, Sijia; Miao, Hang; Qin, Yanru; Liu, Zhaogang; Wang, Jia; Zhang, Haoyang; Lei, Meng; Liu, Jia; Hai, Ou; et al.
Graphical abstract: Abstract: Valosine containing protein (VCP/p97) is a member of the AAA ATPase family involved in several essential cellular functions and plays an important role in the ubiquitin-mediated degradation of misfolded proteins. P97 has a significant role in maintaining the cellular protein homeostasis for tumor cell growth and survival and has been found overexpressed in many tumor types. No new molecule entities based on p97 target were approved in clinic. Herein, a series of novel pyrimidine structures as p97 inhibitors were designed and synthesized. After enzymatic evaluations, structure-activity relationships (SAR) were discussed in detailed. Among the screened compounds, derivative35 showed excellent enzymatic inhibitory activity (IC50, 36 nM). The cellular inhibition results showed that compound35 had good antiproliferative activity against the non-small cell lung cancer A549 cells (IC50, 1.61 μM). Liver microsome stability showed that the half-life of compound35 in human liver microsome was 42.3 min, which was more stable than the controlCB-5083 (25.8 min). The in vivo pharmacokinetic results showed that the elimination phase half-lives of compound35 were 4.57 h for ig and 3.64 h for iv, respectively and the oral bioavailability was only 4.5%. These results indicated that compound35 could be effective for intravenous treatment of non-small cell lung cancer.